KEDUDUKAN UNDANG-UNDANG DAN PERPPU DALAM PERSPEKTIF PENAFSIRAN HUKUM TATA NEGARA - Saputra, Dadin Eka (UIN Antasari, 2015)
Abstract: It is stated in the fourth amendment of 1945 constitution in Article24 C (1) that the Constitutional Court have the power to have final decision/judgment at first and last level to examine Law toward Constitution, to decidethe dispute of authority of state institutions granted by the Constitution, thedissolution of political parties, and the dispute as the results of the elections.Around this time, there are a lot of the problems, especially in the interpretationof the authority given to the Constitutional Court by the Constitution inorder to examine the Law against the Constitution, if it is associated with LawNo. 12 of 2011 on the Establishment of Regulatory of Law, article 7 (1)which states that the type and hierarchy of legislation consists of: a) Constitutionof Republic of Indonesia of 1945; b) Decree of the People’s ConsultativeAssembly; c) Laws/Government Regulation substitute of Law; d)Government Regulation; e) Presidential Decree; f) Provincial Regulation; andg) Regulation of City/District. Therefore, deep analysis study about interpretationof Laws and Government Regulation of substituting law in terms oftheories of Constitutional Law is required.